102 ANOMALOUS ORIGIN OF THE LEFT CORONARY ARTERY WITH DIFFUSE CORONARY HYPOPLASIA RESULTING IN SUDDEN DEATH. (1st January 2005) - Ho, J.; Jevon, G.; Sanatani, S.
Abstract : Background: Sudden death in children and young adults due to cardiac causes is most often related to congenital structural defects of the heart, hypertrophic cardiomyopathy, cardiac conduction system abnormalities, myocarditis or, uncommonly, congenital coronary artery anomalies. Case Description: We report a case of sudden death in a 13 year old boy due to an acute myocardial infarction and arrhythmias following exertion who had had one previous episode of syncope. On autopsy, he was found to have an anomalous origin of the left coronary artery, an acute angle of takeoff of the left coronary artery and diffuse hypoplasia of both the left and right coronary arteries. Both arteries had markedly small lumens throughout their course. The left coronary artery arose from the right coronary sinus, above the sinotubular junction. The proposed mechanism of death was inadequate coronary perfusion as a result of coronary hypoplasia and the anomalous origin of the left coronary artery, resulting in arrhythmias and myocardial infarction. Conclusion: This report provides the first description of this combination of congenital coronary artery abnormalities resulting in sudden death.